Passive continental margin segmentation of the marginal seas and its effect on hydrocarbon accumulation: A case study of the northern continental margin in South China Sea. (January 2021) - Zhang, Gongcheng; Qu, Hongjun; Jia, Qingjun; Zhang, Leigang; Yang, Bo; Chen, Shuo; Ji, Mo; Sun, Rui; Guan, Liming; Hayat, Khizar
Abstract: Global continental marginal basins are often segmented and significantly impact hydrocarbon accumulation. The northern South China Sea is a marginal sea, in which several passive continental marginal basins have been developed. It is represented by the Pearl River Mouth Basin in the eastern part and the Qiongdongnan Basin in the western part, with rich oil and gas resources that exhibit significant differences in hydrocarbon accumulation. However, the impacts on hydrocarbon accumulations due to various segmentations have rarely been discussed. Based on the systematic interpretation of seismic data, paleo-biological data, detailed thickness mappings, sedimentary facies mappings, analyses of organic geochemical characteristics of source rocks, reservoir formation characteristics, and hydrocarbon accumulation patterns, the tectonic segmentation and its effect on hydrocarbon accumulation in the two basins are discussed. The tectonic evolution in the northern part of the South China Sea was characterized earlier in east segmented and later in west segmented; this same pattern is always displayed, wherein the east segmentation occurs one phase earlier than the west segmentation. The tectonic segmentations caused differences in the source rocks, resulting in the formation of two sets of source rocks that were mainly developed in the east basin, namely: the lacustrine source rocks and marine–continental transitional facies coal-series source rocks. Meanwhile, only one set of the marine-continent transitional facies coal-series source rocks and terrestrial marine facies source rocks was developed in the west basin. The segmentations also yielded differences in the reservoir characteristics, even though both basins developed marine–continental transitional facies as well as delta and deep-water gravity flow sandstone reservoirs; meanwhile, the eastern basin developed continental fluvial reservoirs. The differences in hydrocarbon accumulation were controlled by segmentation; at the east basin, structural ridges in shallow layers, deep lithologic–stratigraphic traps, and bulges in sags affected the accumulations of oil and gas. Meanwhile, at the west Qiongdongnan Basin, coal-bearing delta systems produced the gas distributions along the margins of the central subsidence that was adjacent to the source rocks. Graphical abstract: Image 1 Highlights: Disclosure tectonic segmentation rules of continental marginal sea basins. Tectonic segmentations were characterized by being earlier east and later west. Determining impacts of tectonic segmentations on hydrocarbon accumulations. Tectonic segmentations controlled the difference of hydrocarbon accumulations.